Islamic Religious Education With Human Rights And Anti-Violence In Elementary School - Nur Ziadatul Hasanah (AIUA Journal of Islamic Education, 2020)
The issue of human rights and violence is a never ending problem. This is caused by the moral and moral crisis that occurs in humans today. So the need for Islamic religious education with a human rights perspective and anti-violence as an effort to form a person who upholds human rights and avoids acts of violence. The purpose of this study was to determine the design of Islamic religious education materials with human rights and anti-violence perspectives. The method used in this study is the literature review method. The results of the study indicate that in delivering Islamic religious education material with human rights and anti-violence perspectives, teachers need an active role in applying the concept of gentle behavior as an internalization of human rights and anti-violence values to students